First report of the multiresistance gene cfr in Pasteurella multocida strains of avian origin from China. (December 2020) - Chen, Hongmei; Deng, Hui; Cheng, Longfei; Liu, Rongchang; Fu, Guanghua; Shi, Shaohua; Wan, Chunhe; Fu, Qiuling; Huang, Yu; Huang, Xiaohong
Highlights: First report of the multiresistance gene cfr in Pasteurella multocida. IS Apl1 two isolates carrying the cfr gene were multiresistant. Acquisition of the cfr gene was related to the presence of IS 26, IS Apl1 and IS 256. Abstract: Objectives: The aim of this study was to investigate the presence and genetic environment of the multiresistance gene cfr gene in Pasteurella multocida of avian origin from China. Methods: A total of 113 P. multocida isolates were collected from sick poultries (ducks, chickens and geese) from 2003 to 2016 in Southern China and were screened for the presence of the cfr gene by PCR. The cfr -carrying P. multocida strains were subjected to antimicrobial susceptibility testing, S1 nuclease PFGE and Southern blot hybridisation, conjugative transfer and analysis of genetic environment of the cfr gene. Results: Among 113 P. multocida isolates, strains FJ6671 and FJ6683 from Muscovy duck harboured the cfr gene and presented a multiresistant phenotype. The cfr gene in the two strains was located on an ∼40-kb conjugative plasmid in different genetic environments, including IS Apl1 2 – cfr –IS 26 and IS 26 – cfr –IS 256 . Conclusions: These results demonstrate plasmid-carried cfr in P. multocida and suggest that transposition and homologous recombination mediated by IS 26, IS Apl1 and IS 256 might have played an important role in transfer of the cfr gene in P. multocida . To the best of our knowledge, this is the ﬁrst report of the cfr gene in P. multocida . Active and ongoing surveillance of cfr in P. multocida is urgently warranted.